PARTNERSHIP OF SCHOOL-FAMILY-COMMUNITIES AND ITS EFFECT ON STUDENT LEARNING OUTCOMES IN ELEMENTARY SCHOOL KEBUMEN - Suhartono Suhartono; Tri Saptuti Susiani; Ratna Hidayah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This study aims to find out the partnerships implementation among school, family, and communities and its effect on student learning outcomes in elementary school kebumen. This research includes quantitative descriptive research. The subjects in this study was consisted of five elementary schools. The research instruments were questionnaires and interview sheets. Data analysis was carried out using descriptive analysis with a quantitative approach. The results showed that: 1) the implementation of partnerships in elementary schools in Kebumen indicates a good category (B) with a percentage of 82.50%; 2) the partnerships of school-family-comunities in elementary schools  have a significant influence on student learning outcomes.